Manual acupuncture benignly regulates blood-brain barrier disruption and reduces lipopolysaccharide loading and systemic inflammation, possibly by adjusting the gut microbiota - Zhang, Yue; Ding, Ning; Hao, Xin; Zhao, Jun; Zhao, Yali; Li, Yiran; Li, Zhigang (Frontiers in Aging Neuroscience, 2022)
Background Blood-brain barrier (BBB) disruption and gut microbiota dysbiosis play crucial roles in Alzheimer’s disease (AD). Lipopolysaccharide (LPS) stimulation triggered by gut microbial dysbiosis is an important factor in BBB disruption and systemic inflammation, but the mechanism of acupuncture regulation of BBB disruption via the gut microbiota in AD is not clear. Objective The current study evaluated the effect of manual acupuncture (MA) on BBB dysfunction in APP/PS1 mice and examined the mechanism of gut microbiota by acupuncture in AD. Methods Acupoints were applied to Baihui (GV20), Yintang (GV29), and Zusanli (ST36) in the MA group. Mice in the manual acupuncture plus antibiotics (MAa) group received antibiotics and acupuncture, while mice in the probiotics (P) group received probiotics. Alterations in spatial learning and memory, the gut microbiota, tightly connected structure and permeability of BBB, and the expression of LPS and inflammatory factors in each group were assessed. Results Compared to the normal (N) group, cognitive ability was significantly impaired, the gut microbiota composition was markedly altered, the BBB was significantly disrupted, and the expression of LPS in serum and brain, serum TNF-α, and IL-1β were significantly increased in the AD group (p < 0.01). These changes were inhibited in the MA and P groups (p < 0.01 or p < 0.05), and antibiotics reversed the benign regulatory effects of MA (p < 0.01 or p < 0.05). Conclusion Manual acupuncture benignly modulated the gut microbiota and BBB dysfunction, reduced LPS, TNF-α, and IL-1β. These effects were comparable to probiotics. The decrease in LPS load and systemic inflammation may play important roles in the regulation of BBB dysfunction by acupuncture, and the gut microbiota may be a potential target for the benign regulation of BBB disruption by acupuncture.